Exit, voice, constrained loyalty, and entrapment: migrant farmworkers and the expression of discontent on New York dairy farms. Issue 3 (18th May 2016) - Sexsmith, Kathleen
Abstract: This paper analyzes how undocumented migrant farmworkers on New York dairies respond to workplace grievances. In the absence of meaningful recourse to formal labor protections, undocumented Mexican and Guatemalan farmworkers express their dissatisfaction on a moral terrain. Building on Hirschman's "Exit, Voice, and Loyalty" framework, I argue that their responses reveal a gradation of agency, from entrapment on farms with unsupportive employers, constrained loyalty to paternalistic farmers, exit from farms and the dairy sector, to the private and public use of voice . Immigration enforcement pressures, farmer paternalism, and transnational economic obligations to their families at home limit the use of exit and voice. Nevertheless, some farmworkers are re-scaling their use of voice beyond the farm, calling on the public and policy-makers to implement systemic changes that improve their precarious conditions of work and life.